Status Perceraian dan Kebahagiaan pada Wanita di Indonesia - Afrizal, Rafa Fayza; Harmen, Salsabila Yori; Andini, Friska Aulia Dewi (UI Scholars Hub, 2025)
Women’s happiness can be influenced by various factors, including marital status. This study analyzes the relationship between marital status and women's happiness in Indonesia using pooled crossectional data from the Indonesia Family Life Survey (IFLS) wave 4 & 5 in 2007 and 2014. The probit regression method is applied to estimate the impact of marital status on the probability of happiness. Results show that widowed and/or divorced women have significantly lower probabilities of happiness than married women (p-value < 0.01). In addition, the probability of being happy for women who are divorced is higher than those who are widowed (p-value < 0.1). This study also emphasizes that education has an important role in improving women's happiness. The implications of this study suggest the importance of policy interventions to improve access to education for women, particularly for those who are socially and economically vulnerable.